Identification of the dynamic behavior of epoxy material at large strain over a wide range of temperatures. (April 2020) - Bernard, C.A.; Bahlouli, N.; George, D.; Rémond, Y.; Ahzi, S.
Highlights: Dynamic characterization of an epoxy resin over a large range of temperatures. The strain rate and temperature sensitivity of the plastic flow remain limited. Elastic modulus and yield stress show strong sensitivity to the material relaxations. Modeling of the elastic modulus and yield stress is in agreement with the experiments. Abstract: Adhesively bonded joints using epoxy resin are nowadays often replacing welding in offshore applications for safety reasons. During its lifetime, the bonded joint epoxy is submitted to severe environmental and loading conditions, such as humidity, water uptake, thermal aging, and complex loading conditions affecting its mechanical performance. We investigate here the dynamic mechanical behavior of an epoxy resin at large strain over a wide range of temperatures. Analysis of the elastic modulus, yield strain, yield stress and plastic flow as a function of the temperature and strain rate is carried out. Unlike the elastic modulus and the yield stress showing strong sensitivities to the temperature and the strain rate, the plastic flow appears to have a limited sensitivity to the temperature and the strain rate. Numerical modeling is used to determine the yield stress and elastic modulus variations over the glass transition temperature and good agreement is observed between numerical predictions and experimental results.